Detection of toxigenic Clostridioides [Clostridium] difficile: Usefulness of two commercially available enzyme immunoassays and a PCR assay on stool samples and stool isolates - Legaria, María C. (2018)
The best laboratory diagnostic approach to detect Clostridioides [Clostridium] difficile infection (CDI) is a subject of ongoing debate. With the aim of evaluating four laboratory diagnostic methods, 250 unformed stools from patients with suspected CDI submitted to nine medical center laboratories from November 2010 to December 2011, were studied using: (1) an immunochromatographic rapid assay test that combines the qualitative determination of glutamate dehydrogenase (GDH) plus toxins A and B (QAB), the CDIFF QUIK CHEK COMPLETE assay; (2) an enzyme immunoassay for qualitative determination of toxins A and B, the RIDASCREEN™ C. difficile Toxin A/B assay (RAB); (3) a PCR for the toxin B gene assay (PCR); and (4) the toxigenic culture (TC). C. difficile isolates from direct toxin negative stools by QAB, RAB and PCR were evaluated for toxigenicity by the same direct tests, in order to assess the contribution of the TC (QAB-TC, RAB-TC, PCR-TC). A combination of the cell culture cytotoxicity neutralization assay (CCCNA) in stools, and the same assay on isolates from direct negative samples (CCCNA-TC) was considered the reference method (CCCNA/CCCNA-TC). Of the 250 stools tested, 107 (42.8%) were positive by CCCNA/CCCNA-TC. The GDH and PCR/PCR-TC assays were the most sensitive, 91.59% and 87.62%, respectively. The QAB, RAB, QAB/QAB-TC and RAB/RAB-TC had the highest specificities, ca. 95%. A negative GDH result would rule out CDI, however, its low positive likelihood ratio (PLR) of 3.97 indicates that a positive result should always be complemented with the detection of toxins. If the RAB, QAB, and PCR assays do not detect toxins from direct feces, the toxigenic culture should be performed. In view of our results, the most accurate and reliable methods to be applied in a clinical microbiology laboratory were the QAB/QAB-TC, and RAB/RAB-TC, with PLRs >10 and negative likelihood ratios <0.30.